2020
DOI: 10.13106/jafeb.2020.vol7.no11.127
|View full text |Cite
|
Sign up to set email alerts
|

Do Real Interest Rate, Gross Domestic Savings and Net Exports Matter in Economic Growth? Evidence from Indonesia

Abstract: This study aims to measure the effects of real interest rate (RIR), gross domestic savings (GDS), and net exports (EN) shocks on Indonesia's economic growth (EG). The focus on Indonesia is unique due to the abundant resources available in the nation, but they are unsuccessful in boosting economic growth. This study applied a quantitative method to comprehensively analyze the correlation between variables by employing Vector Autoregression Model (VAR) combined with Vector Error Correction Model (VECM). Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…By contrast, the second group are studies that found evidence of negative impact of saving on economic growth (Rahman & Ferdaus 2021;Sabra & Eltalla 2016;Sujianto et al 2020). Among these studies, Agu and Omolade (2021) found that savings have significant negative impact on economic growth in Nigeria both in the short run and the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, the second group are studies that found evidence of negative impact of saving on economic growth (Rahman & Ferdaus 2021;Sabra & Eltalla 2016;Sujianto et al 2020). Among these studies, Agu and Omolade (2021) found that savings have significant negative impact on economic growth in Nigeria both in the short run and the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key variables of interest are GDP which is used as a proxy for economic growth and GDS as a percentage of GDP. Following previous studies, the control variables included in the analysis are: the gross fixed capital formation (GFCF) to GDP a proxy for investment; the Consumer Price Index (CPI) as a proxy for inflation; and Trade openness (TRADE), which is the ratio of total exports plus imports of goods and services to GDP (Joshi et al 2019;Mohanty 2018;Nguyen & Nguyen 2017;Rahman & Ferdaus 2021;Sujianto et al 2020). It is important to highlight that panel data were transformed to natural logarithm to allow the estimates to be analysed as elasticity coefficients.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Terdapat dua cara untuk melihat PDB, yaitu untuk seluruh total perekonomian berasal dari masing-masing individu pada perekonomian serta untuk jumlah belanja terhadap output barang serta jasa ekonomi. Maka disimpulkan bahwa kinerja ekonomi suatu negara dapat dilihat dari tingkat PDB, dan tumbuhnya pergerakan PDB menjadi indikasi atas fenomena pertumbuhan ekonomi dalam suatu negara (Sujianto et al, 2020). Pendapatan negara yang meningkat akan berpengaruh terhadap produktivitas dan kinerja dalam pasar modal.…”
Section: Produk Domestik Bruto (Pdb)unclassified
“…However, there are several other studies that have found different results. Sujianto et al (2020) shows that economic growth negatively responded to net export savings. Kartikasari (2017) found that exports had no effect on economic growth.…”
Section: Introductionmentioning
confidence: 99%